Neighbourhood ghost - Tang, Felice Chai Chin (2009)
A Final Year Project Submitted to the School of Art, Design and Media, Nanyang Technological University in partial fulfillment of the requirements for the Degree of Bachelor of Fine Arts in Digital Filmmaking